Special Needs and Communication in Dentistry Case: Cerebral Palsy (Daniel) - Carly Timmons McKenzie; Stephen C. Mitchell (Association of American Medical Colleges, 2012)
Abstract This resource is a case-based activity created to educate students about caring for medically complex dental patients. It is intended to be used in the first semester of the predoctoral dental students' second year. It aims to familiarize students with the Health Insurance Portability and Accountability Act of 1996 (HIPAA) in the context of electronic information exchange, as well as with writing an official medical consult letter, practicing oral hygiene demonstrations, and researching and formulating a comprehensive periodontal treatment plan. Case-based learning is an effective way to achieve multiple objectives. First, case-based learning, when completed in small groups, facilitates small-group communication and cooperation, as well as encouraging a thorough understanding of concepts. Second, students profess to enjoy working with "real" patients in a safe setting. Third, facilitated small-group discussions offer a less formal, more interactive forum for information exchange.